Los de abajo - Azuela, Mariano, 1873-1952 (Letras mexicanas, 2015)
Demetrio Macias, a peace-loving Indian, becomes caught up in the rebel cause, and climbs the ranks in Pancho Villa's army, only to have the people turn against him in the wake of defeat.